The effect of xylene inhalation on the rat liver - Kükner, Aysel; Canpolat, Leyla; Ozan, Enver; Gökçimen, Alpaslan; Ozan, Sema; Do?rul, Mine (My University, 1997)
In this study, 11284 mg/m3 (2600 ppm) of xylene was administered for 8 hours a day to pregnant rats by means of inhalation, starting from the sixth day of their pregnancies. Furthermore, while a group of non-pregnant rats inhaled the same amount of xylene during the same period, the control group inhaled clean air. Consequently, in addition to the embryotoxic effects of xylene, the effects on the various tissues of the mothers and their litters were observed light and electron microscopes. No external anomalies were observed in any of the rats born at the end of the 21st day, and there were no macroscopic defects in their organs either. While following xylene inhalation no structural defects in the kidney and pancreas was found, expansions in the smooth endoplasmic reticulum of the liver tissues, increases in the lysosomes, and defective mitochondrion structures were found in the pregnant and non-pregnant rats. It was noticed that xylene in particular caused structural defects in the liver of the fetus. Compared to the control groups, increases were observed in the activities of the AST, ALT, ALP, and Arginase enzymes in the liver.
Keywords: Inhalation; Liver; Rat; Xylene